STRUKTUR UKURAN DAN PERTUMBUHAN IKAN DEMERSAL DI PERAIRAN PULAU TAMBELAN-KEPULAUAN RIAU - FAHMI YONVITNER (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Demersal fish were identified to 105 species with lower abundance. For management process, which includes assessment necessary biological data, these fish populations and habitat. Opulasi biology data are examined in this study include the size of the structure, length weight relationship and growth. Analysis of the data distribution approach frequency distribution (Walpole, 1992), length weight relationship (Snedecor, 1967), the growth method Sheperd (Sparee, et al, 1994). It is shown that most fish are fish Leiognathus smallest (5.2 mm), the longest fish Abalistes stellatus (335 mm) and is the most dominant Upeneus asimetricus (70-185 (122.84 ± 18.53)). A total of 63% including negative allometric and isometric rest. Also relatively slow growth rate, which indicates that the fish populations that the pressure on fish resources is higher